"A banana a day keeps wound failure away": comparing the utility of fruit, pig, and synthetic skins for suturing practice. Issue 11 (12th December 2021) - Murphy, Geoffrey; Khan, Muhammad A; Lathif, Adil; Preddy, John
Abstract: Objectives: To investigate how suturing orange and banana peels, pig skin, and synthetic skin compares with the experience of suturing human skin. Design: Interventional study of simple interrupted, vertical mattress, and subcuticular suturing on the four test materials. Participants, setting: Fifteen consultants and six trainees in surgical and emergency medicine specialties at a New South Wales regional teaching hospital. Main outcome measures: The primary outcome was completion of simple interrupted, vertical mattress, and subcutaneous sutures. Secondary outcomes (assessed in a questionnaire) were similarity of suturing each material to suturing human skin, suitability of each material for practising each suture type, and similarity of each material to human anatomic skin types. Results: All 21 participants completed simple interrupted sutures in bananas and pig and synthetic skins, and 15 in orange skin ( P  = 0.002). All 21 participants completed vertical mattress sutures in pig and synthetic skins, 18 in bananas, and six in oranges ( P  < 0.001). The numbers of completed subcuticular sutures were lower for the two fruits (orange, zero; banana, two) than for pig and synthetic skins (each, 21; P  < 0.001). Banana peel was rated as somewhat similar to human skin and recommended for practising simple interrupted and vertical mattress suturing. Conclusions: Bananas are not only useful as healthy snacks between theatre cases, but also for practising and improving simple and vertical mattress suturing skills. However, less portable and nourishing materials are required for subcuticular suturing practice, such as pig skin or synthetic skin.